Septic Abortion and Associated Morbidity and Mortality - Malik, Adiba; Nessa, Kamrun; Begum, Rokeya (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: In Bangladesh a large number of women attending the major urban hospitals with the complications directly due to abortion like, hemorrhage, fever, peritonitis, visceral injuries. Among all types of abortion, septic abortion is a significant health problem with short and long term complications that affect the quality of life of those fortunate enough to avoid mortality. Aim: This study was conducted to assess the septic abortion related morbidity and mortality in a tertiary level hospital in one year. Methods: This study was a cross sectional observational study in the Department of Obstetrics and Gynaecology, Chittagong Medical college hospital form October 2008 to September 2009, where 60 patients of septic abortions in above period were collected by history examination, management, complications and associated morbidity and mortality. Results : 58.3% of septic abortion patients came from lower class, 70% of them were residing in urban slum area, 96.7% were married 44% of them were illiterate, 85% of them did not use any contraceptive methods although they didn't want to increase their family. 78.3% needed surgical treatment, 23.7% needed major surgery like laparotomy, average duration of hospital stay was 12.08 days and 8.33% patients came with septicemic shock and died. Conclusion: Septic abortion is an important contributor to maternal morbidity and mortality, increasing the burden not only the patients but health workers and their resources. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 20-22